THERMOPHOBIC TREHALOSE GLYCOPOLYMERS AS SMART C-TYPE LECTIN RECEPTOR VACCINE ADJUVANTS - NIELSEN, Amy Esther; MANCINI, Rock Joseph; AGUILAR-CARRENO, Hector (2024)
The present disclosure relates to a copolymer comprising at least one PA block and at least one PB block, wherein PA represents a polymer block comprising one or more units of monomer A and PB represents a polymer block comprising one or more units of monomer B, with the monomer A being an amide or ester, and the monomer B being a trehalose-based monomer, wherein at least one hydroxyl group on the trehalose is esterified. The present disclosure also relates to a method of preparing the copolymer and a bioactive agent delivery system comprising the copolymer and a bioactive agent. The present disclosure further relates to a composition comprising the copolymer and a vaccine and a method of vaccinating a subject against infection by an enveloped virus. La présente divulgation concerne un copolymère comprenant au moins un bloc PA et au moins un bloc PB, PA représentant un bloc polymère comprenant une ou plusieurs unités de monomère A et PB représentant un bloc polymère comprenant une ou plusieurs unités de monomère B, le monomère A étant un amide ou un ester, et le monomère B étant un monomère à base de tréhalose, au moins un groupe hydroxyle sur le tréhalose étant estérifié. La présente divulgation concerne également une méthode de préparation du copolymère et un système de distribution d'agent bioactif comprenant le copolymère, ainsi qu'un agent bioactif. La présente divulgation concerne en outre une composition comprenant le copolymère et un vaccin, ainsi qu'une méthode de vaccination d'un sujet contre une infection par un virus enveloppé.